Go with the flow, but keep it stable? The role of flow variability in the context of daily flow experiences and daily creative performance’ - Stollberger, Jakob; Debus, Maike E. (Work and Stress, 2020)
This study investigates the correlates of daily flow experiences at work as well as flow variability (i.e. a person's level of variability in daily flow states) on daily levels of creative performance. Drawing from broaden and build theory, we hypothesised that higher levels of daily flow would be positively related to higher levels of daily creative performance. Extending research on within-person variability of flow experiences, we introduced the concept of flow variability; in particular, we hypothesised that flow variability would be negatively related to a person's creative performance at the day-level. In contrast, based on the notion of heightened reactivity in the context of intra-individual variability, we predicted that the relationship between daily flow and daily creative performance would be stronger among persons with high flow variability. We collected diary data from 44 full-time employees, who provided information on a total of 201 days. Results of multilevel analyses confirmed our predictions. Our study highlights the benefits of examining the different correlates of flow variability across levels, thus revealing an intricate web of cross-level linkages between daily flow states, flow variability, and daily creative performance at work.
CRIS-Team Scopus Importer:2020-04-02
Keywords: creative performance; diary study; Flow experiences; flow variability